A Reliable and Valid Survey to Predict a Patient’s Gagging Intensity - Casey M. Hearing; Rebecca H. Bind; Michael J. Tabacco; Robert M. Hallock (eJournal of Oral Maxillofacial Research, 2014)
Objectives: The aim of this study was to devise a reliable and valid survey to predict the intensity of someone’s gag reflex.